2019
DOI: 10.2147/ijn.s218905
|View full text |Cite
|
Sign up to set email alerts
|

<p>A comparative study: the prospective influence of nanovectors in leveraging the chemopreventive potential of COX-2 inhibitors against skin cancer</p>

Abstract: IntroductionThis study was conducted to elucidate the chemopreventive potential, cytotoxic, and suppression of cellular metastatic activity of etodolac (ETD)-loaded nanocarriers.MethodsTo esteem the effect of charge and composition of the nanovectors on their performance, four types of vectors namely, negative lipid nanovesicles; phosalosomes (N-Phsoms), positive phosalosomes (P-Phsoms), nanostructured lipid carriers (NLCs) and polymeric alginate polymer (AlgNPs) were prepared and compared. ETD was used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The previous results are probably related to the two main limits of the COX inhibitors: low absorption and bioavailability. Additionally, from other studies, it was seen that the prolonged use of COX-2 inhibitors can cause cardiotoxicity [189] and gastrointestinal problems [190] To contrast these limits researchers have studied the possibility of using nanoparticles as vehicles of COX inhibitors [191,192]. The nanoparticle system allows to carrying of the drug to the target site reducing the side effects of the systemic administration and increasing the local concentration.…”
Section: Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…The previous results are probably related to the two main limits of the COX inhibitors: low absorption and bioavailability. Additionally, from other studies, it was seen that the prolonged use of COX-2 inhibitors can cause cardiotoxicity [189] and gastrointestinal problems [190] To contrast these limits researchers have studied the possibility of using nanoparticles as vehicles of COX inhibitors [191,192]. The nanoparticle system allows to carrying of the drug to the target site reducing the side effects of the systemic administration and increasing the local concentration.…”
Section: Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Measurements were performed in triplicate at 25 ± 0.5°C and data were recorded as mean ± SD. 23 In addition, the X-ray diffraction pattern of CuO NPs (prepared using PG) was obtained using a powder X-ray diffractometer (XRD, X`Pert PRO MPD diffractometer, Philips Analytical, The Netherlands) with Cu Ka radiations (k = 1.54060 nm) in 2 h range to guarantee CuO NPs purity.…”
Section: Formulation and Optimization Of Cuo Npsmentioning
confidence: 99%
“…In the other field trial, dogs treated with firocoxib showed significantly greater improvement in osteoarthritis-related pain and lameness, and a significantly reduced incidence of diarrhea relative to dogs treated with etodolac [21]. Currently, there are more and more studies exploring the possibility of using selective COX2 inhibitors in oncological treatment in both animals and humans [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%